2021
DOI: 10.1038/s41598-020-80852-7
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar lordosis morphology correlates to pelvic incidence and erector spinae muscularity

Abstract: The retrospective study aimed to investigate the relationship between lumbar lordosis morphology, pelvic incidence and paraspinal muscle. It enrolled asymptomatic adult volunteers aged between 18 and 45 years old. Lumbar lordosis morphology, consisting of total lumbar lordosis (LL), proximal lumbar lordosis (PLL), distal lumbar lordosis (DLL), lumbar lordosis apex (LLA) and inflexion point, was evaluated, as well as pelvic incidence (PI) and muscularity of erector spinae (ES) and multifidus. Pearson correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…Pesenti et al [16] reported that age was negatively strongly correlated with PLL and PI was positively strongly correlated with proximal lordosis. Li et al [13] revealed that PI had a great correlation with proximal lordosis and the muscularity of erector spinae and multifidus were not correlated with proximal lordosis.…”
Section: Resultsmentioning
confidence: 99%
“…Pesenti et al [16] reported that age was negatively strongly correlated with PLL and PI was positively strongly correlated with proximal lordosis. Li et al [13] revealed that PI had a great correlation with proximal lordosis and the muscularity of erector spinae and multifidus were not correlated with proximal lordosis.…”
Section: Resultsmentioning
confidence: 99%
“…PI = SS + PT. As the sacrum is the entire weight of the spine to rest on, PI is the angle correlating with lumbar lordosis through SS and consequent spine degeneration [ 21 , 24 ]. Although PI has been considered as a static parameter in health individuals, it can be seen that when the sacral inclination changes in destabilized conditions, PI changes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospective studies suggested that distal LL (L4-S1) is comparable between low to moderate and high PI groups. Proximal LL (L1-L4), however, is significantly influenced by the PI value (greater PI, and greater proximal lumbar lordosis) [ 14 , 15 ]. Furthermore, not only does the LL magnitude increase in cases of a larger PI but also the LL apex and inflection point are located more toward the cranial side [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proximal LL (L1-L4), however, is significantly influenced by the PI value (greater PI, and greater proximal lumbar lordosis) [ 14 , 15 ]. Furthermore, not only does the LL magnitude increase in cases of a larger PI but also the LL apex and inflection point are located more toward the cranial side [ 14 ]. Thus, in cases with a large PI the local lordosis around L1, where the conus medullaris is often located [ 1 , 2 , 3 , 4 , 5 , 6 ], might be greater, and the conus medullaris might be located more toward the cranial side in the twisted spinal canal.…”
Section: Discussionmentioning
confidence: 99%